Effect of thymidine on activity of trimethoprim and sulphamethoxazole. Issue 2 (February 1978) - Stokes, A; Lacey, R W
Abstract : Thymidine at levels as low as 0.05 mg/1 reduces the activities of sulphamethoxazole and trimethoprim and their combination in vitro. Using a biological assay procedure, levels of thymidine greater than this were interpreted as being present in urine. The addition of sulphamethoxazole and trimethoprim, singly or in combination, to urine obtained from patients with urinary tract infections showed that all the antibacterial effect towards sensitive organisms was due to the trimethoprim component. It is suggested that trimethoprim should replace the combination co-trimoxazole for the treatment of some lower urinary tract infections, and that laboratory media, if they are to resemble the clinical environment, should contain thymidine.